Respon penawaran pengeluar minyak sawit, getah asli dan koko: Kesan dasar kerajaan - Md Ali, Anizah; Alias, Mohammad; Abdul Rahman, Maria (2000)
The purpose of this paper is to investigate empirically the impact of rural development Government expenditure a proxy for Government policy, on the supply response of Malaysian oil palm, rubber and cocoa producers. Annual data on production and price each commodity for the period 1970-1997 are utilized for the purpose. The supply response function estimation based on economic theory. The hypothesis underlying our study is that there exist a long run relationship between the supply of a commodity and relative price and rural development expenditure. This study employs cointegration method and error correction model (ECM), specifically the Engle-Granger two-step procedure,distinguishing it from earlier studies, which is preceded by an investigation of the stationarity properties of the variables appearing in the supply response equations.The results of the empirical analysis are summarized as follows.First, the supply of palm oil and rubber are found to be cointegrated with its determinants.The long run elasticities of supply for palm oil with respect own price and Government expenditure are significant but unelastic with estimated elasticities 0.17 and 0.26 respectively.In this study the time trend variable is interpreted as a proxy for producers' preference on a particular commodity.The ECM analysis found that the error correction term is significant at the 5 percent level.In the short run, government expenditure and relative price do not Granger cause on palm oil supply, but there exists a long run relationship between supply and its determinants because the coefficient of the error correction term is significant at percent level.Secondly, the long run elasticities of supply with respect to own price, price of palm oil (the substitute crop) and Government expenditure are 0.18-0.13 and 0.22 respectively.A significantly negative coefficient for the time trend variable is interpreted as a negative preference among rubber producers for rubber production compared to oil palm production.The ECM analysis found that the growth in current and lagged price of rubber Granger caused growth in rubber production in the short run.Growth in palm oil weakly Granger cause growth in rubber production in the short run.Growth in palm oil weakly Granger cause growth in rubber supply.The significance of the error correction term is evidence for the existence of a long run relationship between supply of rubber and its determinants (rubber price, palm oil price and development(Government) expenditure).Thirdly, the long run elasticities of supply of cocoa with respect to relative price and Government expenditure are 0.87 and 1.24 respectively.The ECM analysis found that the growth in cocoa price do not Granger cause growth in cocoa supply in the short run.The error correction term is not significant at 5 percent level.There is therefore no long run relationship between supply of cocoa and its determinants.A major policy implication of this study is that public investment is required to revive the fortunes of the natural rubber industry in particular the smallhoding sector.But the injection of Government expenditure has to be substantial as the long run elasticity is relatively low.In the run equation for rubber supply, the coefficient of the price of palm oil variable is significant.Thus other thing remaining the same, the substitution of rubber with palm oil will continue.